The Concept of Truth - Campbell, R. author. aut Link
XI, 260 p.
Keywords: This book addresses the contemporary disillusion with truth, manifest in sceptical relativism. Contending that all contemporary theories of truth are too narrow, it argues for a novel conception of truth, by showing how error is implicated in the actions of all living things; and by analyzing uses of 'true' in non-linguistic contexts.